1996 Annual Report on Exchange Arrangements and Exchange Restrictions : Supplement. (Annual Report on Exchange Arrangements and Exchange Restrictions, 1996)
Published since 1950, this authoritative annual reference is based upon a unique IMF database that tracks exchange and trade arrangements for the 187 IMF member countries, along with Hong Kong SAR, Aruba, and Curacao and St Maarten. The Annual Report on Exchange Arrangements and Exchange Restrictions (AREAER) draws together information on exchange measures in place, the structure and setting of exchange rates, arrangements for payments and receipts, procedures for resident and nonresident accounts, controls on capital transactions, and provisions specific to the financial sector. The 52 countries covered in this special supplement have been selected as those where expanded information on the regulatory framework for capital movements was readily available to the IMF. They include countries that participated in a pilot data collection project on the regulatory framework for capital transactions conducted by the IMF in 1996, and member countries of the OECD.